Chorea-Acanthocytosis Presenting as Autosomal Recessive Epilepsy in a Family With a Novel VPS13A Mutation - Weber, Juliane; Frings, Lars; Rijntjes, Michel; Urbach, Horst; Fischer, Judith; Weiller, Cornelius; Meyer, Philipp T.; Klebe, Stephan (Frontiers in Neurology, 2019)
Chorea-acanthocytosis (ChAc) is a rare, adult-onset disease usually characterized by, hence the name, a movement disorder and acanthocytosis in the blood. It is caused by mutations of the VPS13A gene with an autosomal recessive transmission. We report a consanguineous Turkish family with a different and informative clinical and diagnostic course. Three siblings developed seizures and the index patient had been diagnosed with bilateral temporal lobe epilepsy. A key finding, however, was the basal ganglia involvement in neuroimaging although no movement disorder was present. [18F]FDG-PET showed a prominent decline in striatal glucose metabolism at 31 years of age and [123I]FP-CIT-SPECT revealed a moderate loss of striatal dopamine transporter availability. The family was referred for genetic testing and exome sequencing detected a homozygous novel truncating mutation c.4326 T>A (p.Tyr1442*) in VPS13A in all affected siblings. With this case, we present autosomal recessive epilepsy as the predominant phenotype of ChAc with a new homozygous VPS13A mutation and provide pathological structural and molecular neuroimaging findings.